Homo- and hetero-difunctionalized β-cyclodextrins: Short direct synthesis in gram scale and analysis of regiochemistry - Benkovics, Gábor; Bálint, Mihály; Fenyvesi, Éva; Varga, Erzsébet; Béni, Szabolcs; Yannakopoulou, Konstantina; Malanga, Milo (Beilstein Journal of Organic Chemistry, 2019)
The regioselective difunctionalization of cyclodextrins (CDs) leading to derivatives amenable to further transformations is a daunting task due to challenging purification and unambiguous characterization of the obtained regioisomers with similar physicochemical properties. The primary-side homo-difunctionalization of β-CD can lead to three regioisomers, while the hetero-difunctionalization can generate three pairs of pseudoenantiomers. Previously, approaches with several synthetic steps, expensive reagents, high purification demands and low yields of the products have been employed. Herein we present direct, short and efficient primary-side difunctionalization strategies featuring reproducibility, ease of product purification, scalability of the reactions and versatility of the substituents introduced. Specifically, the prepared ditosylated β-CDs were separated using preparative reversed-phase column chromatography and their structures were elucidated by NMR experiments. Azidation led to the corresponding pure diazido regioisomers. Direct monotosylation of 6-monoazido-β-CD or monoazidation of the single regioisomers 6A,6X-ditosyl-β-CDs afforded hetero-difunctionalized 6A-monoazido-6X-tosyl-β-CDs in significant yields. Overall, the single regioisomers, 6A,6X-ditosyl-, 6A,6X-diazido- and 6A-monoazido-6X-monotosyl-β-CD were prepared in one or two steps and purified in multigram scale thus opening the way towards further selective and orthogonal functionalizations of β-CD hosts.
Keywords: azido-tosyl-cyclodextrin; diazido-cyclodextrin; hetero-difunctionalization; homo-difunctionalization; regioselectivity

(untitled) - Szejtli, J. (Chem. Rev., 1998)

(untitled) - Takashima, Y.; Osaki, M.; Ishimaru, Y.; Yamaguchi, H.; Harada, A. (Angew. Chem., Int. Ed., 2011)

(untitled) - Yuan, D.-Q.; Kitagawa, Y.; Aoyama, K.; Douke, T.; Fukudome, M.; Fujita, K. (Angew. Chem., Int. Ed., 2007)

(untitled) - Dong, S. D.; Breslow, R. (Tetrahedron Lett., 1998)

(untitled) - Řezanka, P.; Navrátilová, K.; Řezanka, M.; Král, V.; Sýkora, D. (Electrophoresis, 2014)

(untitled) - Yao, H.; Qi, M.; Liu, Y.; Tian, W. (Chem. – Eur. J., 2016)

(untitled) - Malanga, M.; Darcsi, A.; Balint, M.; Benkovics, G.; Sohajda, T.; Beni, S. (Beilstein J. Org. Chem., 2016)

(untitled) - Bom, A.; Bradley, M.; Cameron, K.; Clark, J. K.; van Egmond, J.; Feilden, H.; MacLean, E. J.; Muir, A. W.; Palin, R.; Rees, D. C.; Zhang, M. Q. (Angew. Chem., Int. Ed., 2002)

(untitled) - Matsuo, M.; Togawa, M.; Hirabaru, K.; Mochinaga, S.; Narita, A.; Adachi, M.; Egashira, M.; Irie, T.; Ohno, K. (Mol. Genet. Metab., 2013)

(untitled) - Tabushi, I.; Shimokawa, K.; Fujita, K. (Tetrahedron Lett., 1977)

(untitled) - Tabushi, I.; Nabeshima, T.; Fujita, K.; Matsunaga, A.; Imoto, T. (J. Org. Chem., 1985)

(untitled) - Tabushi, I.; Yamamura, K.; Nabeshima, T. (J. Am. Chem. Soc., 1984)

(untitled) - Tabushi, I.; Yuan, L. C.; Shimokawa, K.; Yokota, K.-i.; Mizutani, T.; Kuroda, Y. (Tetrahedron Lett., 1981)

(untitled) - Gramage-Doria, R.; Rodriguez-Lucena, D.; Armspach, D.; Egloff, C.; Jouffroy, M.; Matt, D.; Toupet, L. (Chem. – Eur. J., 2011)

(untitled) - Pearce, A. J.; Sinaÿ, P. (Angew. Chem., Int. Ed., 2000)

(untitled) - Guieu, S.; Sollogoub, M. (J. Org. Chem., 2008)

(untitled) - Ghosh, R.; Zhang, P.; Wang, A.; Ling, C.-C. (Angew. Chem., Int. Ed., 2012)

(untitled) - Xiao, S.; Yang, M.; Sinaÿ, P.; Blériot, Y.; Sollogoub, M.; Zhang, Y. (Eur. J. Org. Chem., 2010)

(untitled) - Sollogoub, M. (Synlett, 2013)

(untitled) - Guieu, S.; Zaborova, E.; Blériot, Y.; Poli, G.; Jutand, A.; Madec, D.; Prestat, G.; Sollogoub, M. (Angew. Chem., Int. Ed., 2010)

(untitled) - Stephenson, R. J.; Wolber, F.; Plieger, P. G.; Harding, D. R. K. (Aust. J. Chem., 2016)

(untitled) - Matsui, Y.; Yokoi, T.; Mochida, K. (Chem. Lett., 1976)

(untitled) - Law, H.; Benito, J. M.; García Fernández, J. M.; Jicsinszky, L.; Crouzy, S.; Defaye, J. (J. Phys. Chem. B, 2011)

(untitled) - Fujita, K.; Matsunaga, A.; Imoto, T. (Tetrahedron Lett., 1984)

(untitled) - Benkovics, G.; Hodek, O.; Havlikova, M.; Bosakova, Z.; Coufal, P.; Malanga, M.; Fenyvesi, E.; Darcsi, A.; Beni, S.; Jindrich, J. (Beilstein J. Org. Chem., 2016)

(untitled) - De Rango, C.; Charpin, P.; Navaza, J.; Keller, N.; Nicolis, I.; Villain, F.; Coleman, A. W. (J. Am. Chem. Soc., 1992)

(untitled) - Gadelle, A.; Defaye, J. (Angew. Chem., 1991)

Proceedings of the IX International Symposium on Cyclodextrins - Djedaini-Pilard, F.; Gosnat, M.; Steinbruckner, S.; Dalbiez, J. P.; Crini, G.; Perly, B.; Gadelle, A. (Santiago de Compostella, 31.5.1998-3.6.1998, 1999)

Conformation of Carbohydrates - Rao, V. S. R. (Harwood Academic Publishers, 1998)

(untitled) - Piras, L.; Theodossiou, T. A.; Manouilidou, M. D.; Lazarou, Y. G.; Sortino, S.; Yannakopoulou, K. (Chem. – Asian J., 2013)

(untitled) - Szemán, J.; Csabai, K.; Kékesi, K.; Szente, L.; Varga, G. (J. Chromatogr. A, 2006)